Relative Advantage and Competitive Pressure towards Implementation of E-commerce: Overview of Small and Medium Enterprises (SMEs) - Sin, Kit Yeng; Abdullah, Osman; Shahrul Nizam, Salahuddin; Safizal, Abdullah; Lim, Yi Jin; Sim, Choon Ling (Science Direct, 2016)
The study of SMEs and E-commerce is acquiring much attention from academicians and practitioners as SMEs play a vital role in generating vast amount of nation’s revenue at present day. Therefore, the contribution of SMEs to economic development inspite of their scarce resources needs intense and passionate study so as to examine the factors which will influence E-commerce adoption among SMEs. Seeing that much research that examines the E-commerce adoption among SMEs and as far as this, researches mainly just concentrate on large firms or organizations, this study aims to analyze the key factors of E-commerce adoption among SMEs in Northern state of Malaysia which comprise of Perlis, Kedah, Penang and Northern part of Perak. Key factors such as relative advantage and competitive pressure are specifically conducted in this research. Above and beyond, this study is conducted based on survey design and descriptive research investigation. Approximately 350 questionnaires are distributed to CEOs or managers diversified from different sectors but only 167 questionnaires were obtained. The research data is analyzed using frequency analysis, reliability analysis, descriptive analysis, correlation analysis as well as multiple regression analysis.